2019
DOI: 10.1073/pnas.1814178116
|View full text |Cite
|
Sign up to set email alerts
|

Modification of excitation and charge transfer in cavity quantum-electrodynamical chemistry

Abstract: Energy transfer in terms of excitation or charge is one of the most basic processes in nature, and understanding and controlling them is one of the major challenges of modern quantum chemistry. In this work, we highlight that these processes as well as other chemical properties can be drastically altered by modifying the vacuum fluctuations of the electromagnetic field in a cavity. By using a real-space formulation from first principles that keeps all of the electronic degrees of freedom in the model explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
202
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(217 citation statements)
references
References 29 publications
9
202
0
Order By: Relevance
“…The resulting consequences can e.g. include a reduced equilibrium bond length [13,14] with an earlier onset of static correlation [14] that could be steered on demand by controlling the polarization of the field and therefore implies interesting opportunities for chemical considerations and electronic devices. Let us briefly inspect how the same system behaves in the Coulomb gauge instead.…”
Section: A No Bound Eigenstates Without Self-polarizationmentioning
confidence: 99%
“…The resulting consequences can e.g. include a reduced equilibrium bond length [13,14] with an earlier onset of static correlation [14] that could be steered on demand by controlling the polarization of the field and therefore implies interesting opportunities for chemical considerations and electronic devices. Let us briefly inspect how the same system behaves in the Coulomb gauge instead.…”
Section: A No Bound Eigenstates Without Self-polarizationmentioning
confidence: 99%
“…Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry. In most of the works published so far, many organic emitters were put into a cavity and the interest was mainly focused on the investigation of collective phenomena between the quantum radiation field and the molecular ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…The strong coupling regime is attractive because in this regime the molecular energy landscape can be radically modified, the regime thus offers great opportunities to control molecular properties. [11][12][13][14] In the past, strong coupling of molecules to cavities has been explored using planar Fabry-Perot resonators, 6,15,16 single plasmonic particles, 17,18 meta-surfaces, 10,19,20 and gap plasmonic cavities, 21 among others.…”
mentioning
confidence: 99%